1997
DOI: 10.3349/ymj.1997.38.6.444
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcal infection in the pathogenesis of BehÇet's disease and clinical effects of minocycline on the disease symptoms

Abstract: Although the precise pathoetiology of Behçet's disease (BD) remains obscure, patients with BD have a high incidence of chronic infectious foci, indicating an enhanced susceptibility to chronic tonsillitis, and dental caries. Sometimes, clinical symptoms appear after treatment of these foci in BD patients. It is believed that BD might be related to an allergic reaction to a bacterial infection in view of the many clinical symptoms, especially the presence of aphthous and genital ulcerations. An attempt to obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 0 publications
2
91
0
Order By: Relevance
“…Thus, hypersensitivity to streptococcal antigens was thought to influence the development of symptoms in patients with Behcet's disease [16,17]. There are few studies investigating the level of ASO in patients with Behcet's disease [15,18].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, hypersensitivity to streptococcal antigens was thought to influence the development of symptoms in patients with Behcet's disease [16,17]. There are few studies investigating the level of ASO in patients with Behcet's disease [15,18].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic symptoms of BD could thus be induced after treatment of dental caries or even by intracutaneous injection of streptococcal antigens. Recent reports have shown that antibacterial treatment is beneficial in BD (8,25).…”
Section: Discussionmentioning
confidence: 99%
“…As one of the triggering factors, the oral unhygienic condition may be suspected, because periodontitis, decayed teeth, chronic tonsillitis, etc. are frequently noted in BD patients [12,13] . The proportion of Streptococcus sanguinis (S. sanguinis), which was previously recognized as species of the genus Streptococcus named "S. sanguis", was significantly high in the oral bacterial flora of BD patients in comparison with those of healthy controls.…”
Section: Introductionmentioning
confidence: 97%
“…Although the actual etiology of BD is still unclear, the pathogenesis has been generally clearer by the etiological studies based on the genetic intrinsic factors and extrinsic triggering factors [5][6][7][8][9][10][11][12][13][14][15][16] . As one of the triggering factors, the oral unhygienic condition may be suspected, because periodontitis, decayed teeth, chronic tonsillitis, etc.…”
mentioning
confidence: 99%